Editing of the urease gene by CRISPR-Cas in the diatom Thalassiosira pseudonana. Issue 1 (December 2016) - Hopes, Amanda; Nekrasov, Vladimir; Kamoun, Sophien; Mock, Thomas
Abstract Background CRISPR-Cas is a recent and powerful addition to the molecular toolbox which allows programmable genome editing. It has been used to modify genes in a wide variety of organisms, but only two alga to date. Here we present a methodology to edit the genome ofThalassiosira pseudonana, a model centric diatom with both ecological significance and high biotechnological potential, using CRISPR-Cas. Results A single construct was assembled using Golden Gate cloning. Two sgRNAs were used to introduce a precise 37 nt deletion early in the coding region of the urease gene. A high percentage of bi-allelic mutations (≤61.5%) were observed in clones with the CRISPR-Cas construct. Growth of bi-allelic mutants in urea led to a significant reduction in growth rate and cell size compared to growth in nitrate. Conclusions CRISPR-Cas can precisely and efficiently edit the genome ofT. pseudonana . The use of Golden Gate cloning to assemble CRISPR-Cas constructs gives additional flexibility to the CRISPR-Cas method and facilitates modifications to target alternative genes or species.